Patient, sufferer, victim, casualty or person with cervical myelopathy: let us decide our identifier. Issue 1 (25th June 2020) - Boerger, Timothy F; Davies, Benjamin M; Sadler, Iwan; Sarewitz, Ellen; Kotter, Mark R N
Abstract : Among biomedical journals, person-first language is considered preferable to identity person-first language. However, not all populations of people with certain medical diagnoses, such as deafness, prefer person-first language. Moreover, adherence to person-first language is poor among the literature on some neurological diagnoses. Therefore, it is most appropriate to consult with people with a given diagnosis regarding their preferred identifier. Here, we describe a consensus process undertaken by the REsearch objectives and COmmon Data Elements for Degenerative Cervical Myelopathy (RECODE-DCM, recode-dcm.com ) steering committee members with cervical myelopathy to determine our preferred identifier.